The Study of the Morphobiological Properties of Tomatoes (Eurasian Research Bulletin, 2022)
Tomato fruit - a multi-celled, multi-seeded, fleshy berry. Fruits vary in weight: from 20- 50 g to 500-800 g. Weight is small to 70 g, 70-100 g - medium, heavier than 100 g - large. Tomato fruits are flat, flat round, round, oval, noxious, elongated cylindrical and so on in shape.